Chemical Profiling, in-vitro biological evaluation and molecular docking studies of Ruellia tweediana: An unexplored plant - Shamsa Kanwal; Saeed Ahmad; M. Yasmin Begum; Ayesha Siddiqua; Huma Rao; Bilal Ahmad Ghalloo; Muhammad Nadeem Shahzad; Imtiaz Ahmad; Kashif-ur-Rehman Khan (Saudi Pharmaceutical Journal, 2024)
Many Ruellia species have been utilized in traditional medicine and despite the prevalent use of Ruellia tweediana in folk medicine, its antioxidant potential and polyphenol content have not been investigated. Therefore, the present study aimed to explore the medicinal value of R. tweediana by evaluating its total phenolic (TPC) and flavonoid contents (TFC), GC–MS analysis, antioxidant, antibacterial, and enzyme inhibition activities. The TPC and TFC of the extract/fractions were assessed using the Folin-Ciocalteu and aluminum trichloride methods, respectively. To determine the antioxidant capacity, five different assays were used: DPPH, ABTS, CUPRAC, FRAP, and metal chelating assays. The inhibition activity against α-glucosidase, α-amylase, cholinesterases, and lipoxygenase enzymes was also analyzed. Furthermore, GC–MS was performed for chemical screening of non-polar fraction. The methanol extract showed the maximum TPC (167.34 ± 2.23 mg GAE/g) and TFC (120.43 ± 1.71 mg RE/g) values among all the tested samples. GC–MS screening of the n-hexane fraction showed the presence of 40 different phytoconstituents. The results demonstrated the highest scavenging potential of the methanol extract against DPPH (167.79 ± 2.75 mg TE/g) and ABTS (255.32 ± 2.91 mg TE/g) radicals, as well as the metal-reducing capacity measured by CUPRAC (321.34 ± 3.09 mg TE/g), FRAP (311.32 ± 2.91 mg TE/g), and metal chelating assay (246.78 ± 10.34 mg EDTAE/g). Notably, the n-hexane fraction revealed the highest α-glucosidase and α-amylase inhibition activity (186.8 ± 2.84 and 179.7 ± 4.32 mg ACAE/g, respectively) while methanol extract showed highest acetylcholinesterase and butyrylcholinesterase inhibition activity (198.6 ± 3.31 and 184.3 ± 2.92 mg GALE/g, respectively). The GC–MS identified Lupeol showed best binding affinity with all docked enzymes as compared to standard compounds. The presence of bioactive phytoconstituents showed by GC–MS underscores the medicinal importance of R. tweediana, making it a promising candidate for natural medicine.